HOW CAN ENVIRONMENTAL DISPUTE RESOLUTION BE RESOLVED WITHOUT GOING TO COURT - Pandiangan, Leo Nora Elly AM; Koeswidi, Nanin; Silitonga, Norti Retiana (Jurnal Hukum dan Peradilan, 2021)
To protect environmental pollution and/or damage, the government has issued legislation on environmental protection and management supplemented by Ministerial Regulations. Environmental pollution and/or damage can occur due to natural factors and human actions that result in losses to the country and/or society. Environmental polluters and/or destroyers can be prosecuted in court. Before environmental disputes are transferred to court, environmental disputes are first resolved through mediation conducted by a mediator and settled out of court (non-litigation) in accordance with applicable laws. Mediators or the role of third-party services are free and neutral /impartial.